INTERACTION OF SOIL-CEMENT PILE SUPPORTING STRUCTURES WITH THE BODY OF A LANDSLIDE - Ihnatenko, D. Y.; Petrenko, V. D.; Tiutkin, O. L. (Science and Transport Progress, 2017)
Purpose. Analysis and comparison of the landslide slope finite element model calculation results of the appliance of soil-cement piles, depending on the variation of the retaining structure rigidity, makes it possible to evaluate the effectiveness of their application and the cooperative work of piles with the displacement body. It also makes it possible to make a conclusion about the advantages of using this anti-landslide protection method of the slope. Methodology. Analysis of geomorphological data obtained from the results of laboratory studies of soils on the slope section is considered. Creation of a three-dimensional finite-element slope model according to the constructed sections and depths of the soil layers. Calculation of the nonlinear problem of finite element modeling of the slope with applying of soil-cement piles of various rigidity. Findings. The obtained results of calculating the finite element model of the landslide slope, and the analysis of the stress-strain state of the construction with soil-cement piles has been carried out. Originality. Despite the widespread of using soil-cement piles as enclosing structures for the construction of foundation pits and reinforcement of foundations of emergency structures, special attention should be paid to the study of the expediency of using soil-cement retaining pile structures on landslide areas. Practical value. It is known that soil-cement retaining piles are expediently in use as a protective element, which interacts quite well with the ground environment due to its structure of the initial material. Using of modern computer programs of finite element modeling makes it possible to calculate the efficiency of the use of soil-cement piles and to determine the parameters of the necessary retaining structure according to the given geological structure of the slope, and also, depending on its shape and the physical characteristics of the soils, to compare the performance of different protective landslide structures types.